Contribution of PGE2 EP1 receptor in hemin-induced neurotoxicity - Mohan, Shekher; Glushakov, Alexander V.; deCurnou, Alexander; Narumiya, Shuh; Doré, Sylvain (Frontiers in Molecular Neuroscience, 2013)
Although hemin-mediated neurotoxicity has been linked to the production of free radicals and glutamate excitotoxicity, the role of the prostaglandin E2 (PGE2)-EP1 receptor remains unclear. Activation of the EP1 receptor in neurons results in increased intracellular calcium levels; therefore, we hypothesize that the blockade of the EP1 receptor reduces hemin neurotoxicity. Using postnatal primary cortical neurons cultured from wild-type (WT) and EP1-/- mice, we investigated the EP1 receptor role in hemin neurotoxicity measured by lactate dehydrogenase (LDH) cell survival assay. Hemin (75 µM) induced greater release of LDH in WT (34.7 ± 4.5%) than in EP1-/- (27.6 ± 3.3%) neurons. In the presence of the EP1 receptor antagonist SC-51089, the hemin-induced release of LDH decreased. To further investigate potential mechanisms of action, we measured changes in the intracellular calcium level [Ca2+]i following treatment with 17-phenyl trinor PGE2 (17-pt-PGE2) a selective EP1 agonist. In the WT neurons, 17-pt-PGE2 dose-dependently increased [Ca2+]i. However, in EP1-/- neurons, [Ca2+]i was significantly attenuated. We also revealed that hemin dose-dependently increased [Ca2+]i in WT neurons, with a significant decrease in EP1-/- neurons. Both 17-pt-PGE2 and hemin-induced [Ca2+]i were abolished by N-methyl-D-aspartic acid receptor and ryanodine receptor blockers. These results suggest that blockade of the EP1 receptor may be protective against hemin neurotoxicity in vitro. We speculate that the mechanism of hemin neuronal death involves [Ca2+]i mediated by N-methyl-D-aspartic acid receptor-mediated extracellular Ca2+ influx and EP1 receptor-mediated intracellular release from ryanodine receptor-operated Ca2+ stores. Therefore, blockade of the EP1 receptor could be used to minimize neuronal damage following exposure to supraphysiological levels of hemin.